Nanocomposites of nickel phthalocyanines as electrocatalysts for the oxidation of chlorophenols an experimental and theoretical approach - Khene, Mielie Samson (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
In this work the interaction between peripherally (b) substituted nickel tetrahydroxyphthalocyanines (b-NiPc(OH)4 and poly-b-Ni(O)Pc(OH)4) with 4-chlorophenol is theoretically rationalized by performing calculations at the B3LYP/6-31G(d) level. Density functional theory (DFT) and molecular orbital theory are used to calculate the condensed Fukui function for phthalocyanine derivatives and 4-chlorophenol, in order to determine the reactive sites involved when 4-chlorophenol is oxidized, and to compare theoretically predicted reactivity to experimentally determined electrocatalytic activity. Electrocatalytic activities of adsorbed NiPc derivatives: OPGE-Î±-NiPc(OH)8 (OPGE = ordinary pyrolytic graphite electrode, Î± = nonperipheral substitution), OPGE-a-NiPc(OH)4 and OPGE-Î²- NiPc(OH)4 are compared with those of the polymerized counterparts: OPGE-poly-Î±-Ni(O)Pc(OH)8, OPGE poly-a-NiPc(OH)4 and OPGE-poly-Î²-NiPc(OH)4, respectively. Î²-NiPc(NH2)4, Î²-NiPc(OH)4, Î±-NiPc(OH)4, Î±-NiPc(OH)8, Î±-NiPc(C10H21)8 are adsorbed on singled walled carbon nanotube (SWCNT) and Î²-NiPc(NH2)4-SWCNT (linked to SWCNT), are used to modify glassy carbon electrode (GCE) and employed for the electro oxidation of chlorophenols. The Î²-NiPc(NH2)4-SWCNT gave the best current response for the oxidation of 4-chlorophenol. Î±-NiPc(OH)8-SWCNT and Î±-NiPc(C10H21)8 gave the best resistance to electrode fouling due to oxidation by product of 4-chlorophenol. The synthesis of conjugates of cadmium telluride quantum dots (CdTe-QDs) capped with thioglycolic acid and peripherally substituted nickel tetraamino phthalocyanine (Î²-NiPc(NH2)4) complex were also employed for the oxidation of chlorophenols. Separation of one of the diastereomers of 1, 2-subnaphthalocyanine (SubNPc) was achieved as well as separation of the enantiomers. The absorption and magnetic circular dichroism spectra, together with theoretical calculations, reveal rather small variations in the frontier molecular orbitals of the SubNPc compared to conventional subphthalocyanine (SubPc), except for the destabilization of the highest occupied molecular orbital (HOMO), which results in a characteristic absorption in the Soret band region. The chirality of SubNPc, including the cyclic dichroism (CD) signs and intensities, are discussed in detail.
Keywords: Nanocomposites (Materials) -- Research; Phthalocyanines -- Research; Chlorophenols -- Research; Electrocatalysis -- Research